Technology usage and glycaemic outcomes in a single tertiary centre with an ethnically diverse and socioeconomically deprived cohort of children with type 1 diabetes mellitus - Dickinson, India; Gupta, Ankita; Lau, Gar Mun; Iyer, Pranav Viswanath; Pemberton, John Stuart; Uday, Suma (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundThe UK National Paediatric Diabetes Audit (NPDA) data reports disparities in Haemoglobin A1c (HbA1c) levels among children and young people (CYP) with Type 1 Diabetes (T1D), with higher levels in those of Black ethnic background and lower socioeconomic status who have less access to technology. We investigate HbA1c differences in a T1D cohort with higher than national average technology uptake where > 60% come from an ethnic minority and/or socioeconomically deprived population.Design & methodsRetrospective cross-sectional study investigating the influence of demographic factors, technology use, and socioeconomic status (SES) on glycaemic outcomes. The study population was 222 CYP with T1D who attended the diabetes clinic in 2022 at a single tertiary paediatric diabetes centre.ResultsAmong 222 CYP, 60% were of ethnic minority (Asian, Black, Mixed and Other were 32%, 12%, 6% and 10% respectively) and 40% of white heritage. 94% used Continuous Glucose Monitoring (CGM) and 60% used Continuous Subcutaneous Insulin Infusion (CSII) via open or closed loop. 6% used Self-Monitoring of Blood Glucose (SMBG) and Multiple Daily Injections (MDI), 34% used CGM and MDI, 38% used CGM and CSII and 22% used Hybrid Closed-Loop (HCL) systems. Significant differences in HbA1c across therapy groups (p < 0.001) was noted with lowest HbA1c in HCL group (55 mmol/mol; p <0.001). Despite adjusting for therapy type, the Black group had higher HbA1c than their white and Asian counterparts (p<0.001). CYP from the most deprived tertile had significantly higher HbA1c levels (p < 0.001) but the difference was not sustained after adjusting for therapy type.ConclusionAdvanced diabetes technologies improve glycaemic control. Whilst equalising technology access mitigates socioeconomic disparities in HbA1c, CYP from Black ethnic background continue to display a higher HbA1c. The study underscores the necessity of fair technology distribution and further research into elevated HbA1c levels among Black CYP using advanced diabetes technology.